2013
DOI: 10.1080/15623599.2013.10878226
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Failure of Small Contractors in Saudi Arabia

Abstract: The construction industry in Saudi Arabia is currently flourishing due to increased earned revenues from the oil industry. Small contractors are finding more opportunities for business. The objective of this paper is to understand the reasons behind failure of small contractors and identify the most important factors contributing to their failure. A questionnaire survey was developed and distributed among 43 small contractors for obtaining their feedback and to assess the most critical reasons behind failure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Poor Accounting System and Records;-was ranked ninth with the mean score of 3.33, conforming with the studies by Assaf, Srour & Hassanain (2013); Adjei et al (2018), who insist that; financial related issues such as high interest rates paid, poor financial accounting system and records, mismanagement of cash flow, poor debt collection are among the most hostile challenges, that cause the failure of SMSBCs in developing countries. Moreover, poor cost planning of both parties due to lack of proper budgeting, and hence resulting to poor quality of work, was also shared by the respondents.…”
supporting
confidence: 74%
“…Poor Accounting System and Records;-was ranked ninth with the mean score of 3.33, conforming with the studies by Assaf, Srour & Hassanain (2013); Adjei et al (2018), who insist that; financial related issues such as high interest rates paid, poor financial accounting system and records, mismanagement of cash flow, poor debt collection are among the most hostile challenges, that cause the failure of SMSBCs in developing countries. Moreover, poor cost planning of both parties due to lack of proper budgeting, and hence resulting to poor quality of work, was also shared by the respondents.…”
supporting
confidence: 74%
“…The RII, as a recognized research methodology was adopted for assessing the importance level of each of the identified factors (Assaf et al , 2013, 2015; Hassanain et al , 2014, 2015; Sha’ar et al , 2017). Upon receiving and tabulating the assessment of the factors, the RII for each factor was computed with the aid of the following formula (Badu et al , 2013): where a i is the constant representing the weight assigned to i , and x i is a variable representing the frequency assigned to i .…”
Section: Assessment Of Factors Affecting the Maintenance Cost Of School Facilitiesmentioning
confidence: 99%
“…The authors opted to use a recognized research methodology adopted in several studies (Assaf et al , 2013, 2015; Hassanain et al , 2014a, b; Sha’ar et al , 2017). The identified 20 causes for DDDs have undergone 10 initial quality checks through the interviews, and then pilot-testing, before being assessed by the domain specialists.…”
Section: Assessment Of the Causes Of Dddsmentioning
confidence: 99%